Caracterização dos aspectos físicos e populacionais do bairro Jardim Primavera na cidade de Sumaré, SP: considerações sobre vulnerabilidade a inundações - Rau, Sophia Helene Marin [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The urban expansion, combined with the current and intense degeneration of the environment and its ecosystems, has increased the risks of environmental disasters lately. It is imperative to do a work of disaster analysis, regardless of where the events occur and the social situation of the people who live there. The science of vulnerability is an important instrument for the elaboration of public policies, aiming at the prevention and mitigation of natural disasters, and has been adopted in Brazil and in the world as a tool in the planning of risk reduction policies. Considering this, it is essential to look for ways to analyze the factors that cause disasters, identify risk situations and seek possible solutions that solve or attenuate such problems. This study aimed to analyze the current situation of the urban area of Jardim Primavera neighborhood in the municipality of Sumaré. Based on the use of basic data from the Brazilian Institute of Geography and Statistics (IBGE, 2010) and fieldwork with interviews, the physical and social aspects of the site have been characterized and analyzed. The study was based on works that sought to characterize areas vulnerable to flooding and mapping areas at risk to these events. Looking for a deepening of the analysis, the results interacted with thematic maps of the municipality. Based on the census data, it is concluded that the percentage of elderly people in the neighborhood is 11.27%, relatively low compared to that of Brazil as a whole and that of each region of the country, except for the North. The Population Aging Index - IEP is relatively high when compared to Brazil and each of its regions. Furthermore, it was possible to observe that in Jardim Primavera neighborhood the percentage of the population in the age range of the so-called PEA, Economically Active Population, is significantly high. The birth rate of the municipality is not as high as in extremely poor localities; however, is not as...

A expansão urbana, combinada com a atual e intensa degeneração do meio ambiente e seus ecossistemas, tem tornado maiores os riscos de desastres ambientais. Um trabalho de análise dos desastres é imprescindível, independentemente de onde for o local onde esses eventos ocorrem e qual a situação social das pessoas que ali habitam. A ciência da vulnerabilidade é um importante instrumento para a elaboração de políticas públicas, visando a prevenção e mitigação de desastres naturais, a qual vem sendo adotada no Brasil e no mundo como uma ferramenta no planejamento de políticas de redução de risco. Levando isso em conta, é essencial procurar formas de analisar os fatores que causam os desastres, identificar situações de risco e buscar possíveis soluções que resolvam ou amenizem tais problemas. Este trabalho teve como objetivo analisar a atual situação da área urbana do bairro Jardim Primavera no município de Sumaré. A partir do uso de dados de base do Instituto Brasileiro de Geografia e Estatística (IBGE) e trabalhos de campo com entrevistas, foi feita a caracterização e a análise de aspectos físicos e populacionais do local estudado. O estudo se apoiou em trabalhos que buscaram fazer a caracterização de áreas vulneráveis a inundações e mapeamentos de áreas de risco a esses eventos. Os resultados interagiram com mapas temáticos do município. A partir da análise de dados censitários, conclui-se que a porcentagem de idosos no bairro é de 11,27%, relativamente baixa se comparada à do Brasil como um todo e à de cada região do país, exceto a região Norte. O Índice de Envelhecimento Populacional - IEP é relativamente alto se comparado ao do Brasil e de cada uma de suas regiões. Ademais, foi possível observar que no bairro Jardim Primavera a porcentagem da população na faixa etária da chamada PEA, População Economicamente Ativa, é significantemente alta. A taxa de natalidade do município não...
Keywords: Geografia física; População; Inundações; Geografia urbana; Crescimento urbano; Catástrofes naturais; Políticas públicas; Sistemas de informação geográfica; Sumaré (SP); Brasil